2011
DOI: 10.5296/ijl.v3i1.987
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies: A Key Factor to Improvement of TOEFL Candidates’ Reading Comprehension Ability

Abstract: Many studies have been conducted to explore language learning strategies and their relations or effects on learners' performances (Prokop, 1989;Oxford, 1990;Gallo-Crail & Zerwekh, 2002).This small-scale study tries to explore the full range to learning achievement, with an emphasis on the skill of reading. Reading comprehension is highly emphasized for either exam-taking or academic purpose in most English classrooms. The study determines whether cognitive learning strategies have any effect on the improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…In other words, students' comprehension ability enhanced when they used the mentioned strategy in comprehending the passages. This study is in line with the previous studies which have been done over the past 20 years stressing that learning strategies improve students' language skills particularly their reading skill and help them make progress in their reading tasks ( [2]; [27]; [28]; [29]; [30]). To sum up the final results of the study, the current study attempted to answer the following research question.…”
Section: Resultssupporting
confidence: 91%
“…In other words, students' comprehension ability enhanced when they used the mentioned strategy in comprehending the passages. This study is in line with the previous studies which have been done over the past 20 years stressing that learning strategies improve students' language skills particularly their reading skill and help them make progress in their reading tasks ( [2]; [27]; [28]; [29]; [30]). To sum up the final results of the study, the current study attempted to answer the following research question.…”
Section: Resultssupporting
confidence: 91%
“…In past years studies show that learning note-taking strat-egies improve students' reading skills and precisely are use-ful to make progress in reading tasks of their lessons (O'Mal-ley & Chamot, 1990;Carrel, 1998;Taraban, 2004;Phakiti, 2006;Motallebzadeh & Mamdoodi, 2011). For instance, one study in 2005 showed that taking note was beneficial in high-er achievement and also effective to remember the contents that students read.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Educators have verified that scanning is an effective strategy in enhancing reading comprehension (Motallebzadeh and Mamdoohi, 2011). There are two important aspects in the scanning strategy: keywords and their corresponding scopes.…”
Section: Anticipate In What Form the Information Ismentioning
confidence: 96%